Philanthropy : Developing a Productive Zakat-Based UMKM Empowerment Model at Baznas of Pekanbaru City - Delima Afriyanti; Ahda Segati; Landes Yuanda (International Journal of Economics, Commerce, and Management, 2024)
Productive zakat is one of the instrument potential Islamic philanthropy in empowerment economy society, especially UMKM actors. Research This aiming For developing a model for empowering Micro, Small, and Medium Enterprises (MSMEs) based on productive zakat at Collection Agency (BAZNAS) of Pekanbaru City. Research This using approach qualitative with method studies cases in BAZNAS Pekanbaru City. Data collected through interview in-depth, observation, and documentation. Research results show that zakat is productive can become solution strategic in development of MSMEs with provide business capital, mentoring and training for mustahik. The proposed empowerment model covering a number of stages , namely identification mustahik potential , assessment eligibility effort , giving capital assistance , mentoring efforts , and evaluation sustainability business . Implementation of this model expected can increase capacity and independence economy mustahik, and optimize management of productive zakat at BAZNAS. With development of this model , BAZNAS Pekanbaru City expected can more effective in operate his role as institution zakat managers who do not only focuses on the distribution of consumptive zakat , but also plays a role active in empowerment economy people through productive zakat . Research This give contribution practical and theoretical in field Islamic philanthropy and empowerment economy, as well as become reference for other zakat institutions in optimize productive use of zakat For support growth of MSMEs.